Rapid Particle Swarm Optimization Algorithm for Solving Optimal Reactive Power Dispatch Problem - Kanagasabai Lenin; B. Ravindhranath Reddy; M. Surya Kalavathi (IAES Indonesian Section, 2017)
In this paper Rapid Particle Swarm Optimization (RPSO) algorithm is proposed to solve the optimal reactive power dispatch Problem. The Rapid Particle swarm Optimization (RPSO) algorithm is obtained by merging PSO with Cauchy mutation. Basic idea is to introduce the Cauchy mutation into PSO such that it prevents PSO from trapping into a local optimum through stretched jumps made by the Cauchy mutation. In order to evaluate the efficiency of the proposed algorithm, it has been tested on IEEE 30 bus system and compared other standard algorithms. Results show’s that RPSO is more efficient in reducing the real power loss and voltage index also improved.